2010
DOI: 10.1093/brain/awq179
|View full text |Cite
|
Sign up to set email alerts
|

Functional role of brain-derived neurotrophic factor in neuroprotective autoimmunity: therapeutic implications in a model of multiple sclerosis

Abstract: Brain-derived neurotrophic factor plays a key role in neuronal and axonal survival. Brain-derived neurotrophic factor is expressed in the immune cells in lesions of experimental autoimmune encephalomyelitis and multiple sclerosis, thus potentially mediating neuroprotective effects. We investigated the functional role of brain-derived neurotrophic factor in myelin oligodendrocyte glycoprotein-induced experimental autoimmune encephalomyelitis, an animal model of multiple sclerosis. Mice deficient for brain-deriv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
166
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 191 publications
(183 citation statements)
references
References 66 publications
13
166
1
3
Order By: Relevance
“…In this article, we found that cortistatin protected oligodendrocytes from cell death in an oxidative milieu as occurs in EAE. Moreover, cortistatin increased the local levels of BDNF and ADNP, which induce axonal outgrowth, remyelination, and rescue of degenerating neurons (24,25). For ADNP, this effect is exerted on both peripheral lymphoid cells and resident CNS cells.…”
Section: Discussionmentioning
confidence: 96%
“…In this article, we found that cortistatin protected oligodendrocytes from cell death in an oxidative milieu as occurs in EAE. Moreover, cortistatin increased the local levels of BDNF and ADNP, which induce axonal outgrowth, remyelination, and rescue of degenerating neurons (24,25). For ADNP, this effect is exerted on both peripheral lymphoid cells and resident CNS cells.…”
Section: Discussionmentioning
confidence: 96%
“…Transgenic mice with BDNF depletion in either astrocytes or immune cells show enhanced disease severity associated with axonal loss (Linker et al, 2010), suggesting a BDNF-mediated neuroprotective mechanism. However, neurotrophins have a Janus-like nature as they may also induce neuronal death in vitro (Friedman, 2000), and heterozygous BDNF /+ mice, which display half-normal BDNF levels, show ameliorated EAE (Javeri et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Our observations also raise the possibility that several different mechanisms contribute to the oligodendrotrophic effect of myelin-specific T cells. In addition to IFN-␥, subpopulations of T cells in inflammatory lesions produce BDNF, 84 -86 which in addition to its multiple beneficial effects on neurons 87 is a potent stimulus of remyelination 88 and neuronal plasticity. 49 That we did not detect BDNF mRNA expression in vitro suggests that BDNF in vivo is produced by CNS neurons and glial cells, which is in line with in situ hybridization studies that demonstrated high BDNF mRNA expression, in particular in hippocampal neurons.…”
Section: Discussionmentioning
confidence: 99%